Confectionery products (halva type) obtained from sunflower: production technology and quality alterations. A review - Mureşan, V.; Blecker, C.; Danthine, S.; Racolţa, E.; Muste, S. (Biotechnologie, Agronomie, Société et Environnement, 2013)
Sunflower "halva" is a popular and widely enjoyed confectionery product specific to the countries of Eastern Europe. Conventional halva has historically been produced from sesame seeds in the Middle East and Northern Africa. However, in the production of halva in Eastern Europe, sesame seeds have been largely replaced by sunflower seeds, due to the high availability of sunflower in this region and the comparable taste of the final product. Due to the importance of the cost of raw materials in the food industry, utilization of sunflower seeds in halva production may be of great interest worldwide because it offers the possibility of significantly lowering production costs. Nevertheless, oil separation and storage techniques must be perfected if sunflower halva is to fulfill its promise of becoming a cost effective alternative to sesame seed halva on a worldwide scale. The aims of this review are firstly, to describe the current state of sunflower halva technology, secondly, to isolate the main problems affecting the quality of the final product, and thirdly, to suggest areas of further research necessary to move sunflower halva production closer to reaching its full potential on the world market.